Living fossils : clues to the past - Arnold, Caroline (Charlesbridge, 2016)
Introduces "living fossils, or modern-day animals that very closely resemble their ancient relatives. Meet the coelacanth, horseshoe crab, dragonfly, tuatara, nautilus, and Hula painted frog. All are living fossils. Why have they changed so little over time, while other animals evolved or went extinct?"--Amazon.com.